Effect of Side Groove on Shear Lips Formation of Aluminium Alloy 6061 using Finite Element Analysis - Asry, Mohd Azmeer; Harimon, Mohd Azhar (Journal of Advanced Mechanical Engineering Applications, 2021)
Aluminium alloys are commonly utilised to reduce the weight of vehicles as structural components due to their good mechanical properties, lightweight characteristics, ease of fabrication, and high specific strength. During an accident, aluminium alloys are subjected to high velocity and varying loads. As a result, it is crucial to understand the impact properties of aluminium alloys. The side groove influence on the shear lip development of the aluminium alloy Al6061 was investigated in this study. The Charpy impact test under different side groove depth ratio was conducted through simulation using Abaqus. It was found that the shear lips ratio decreased when the side groove depth ratio increased. The energy absorption and force required to fracture the specimen decreased when the side groove depth ratio increased. As a result of the lower shear lips ratio, less absorb energy, and less force of impact, increasing the side groove depth ratio will tend to lower Al6061 ductility.